2007
DOI: 10.1086/518796
|View full text |Cite
|
Sign up to set email alerts
|

Increase in HCV Incidence among Men Who Have Sex with Men in Amsterdam Most Likely Caused by Sexual Transmission

Abstract: We retrospectively screened 1836 men who have sex with men (MSM) participating in the Amsterdam Cohort Studies (1984-2003) for hepatitis C virus (HCV) antibodies. HCV incidence was 0.18/100 person-years (PY) in human immunodeficiency virus (HIV)-positive MSM (8/4408 PY [95% confidence interval {CI}, 0.08-0.36]) but was 0/100 PY in MSM without HIV (0/7807 PY [95% CI, 0.00-0.05]). After 2000, HCV incidence among HIV-positive men increased 10-fold to 0.87/100 PY (5/572 PY [95% CI, 0.28-2.03]). Additional hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
190
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(214 citation statements)
references
References 42 publications
19
190
0
5
Order By: Relevance
“…Molecular typing of HCV isolates confirmed the presence of MSM-specific transmission networks in London [25], Paris [26] and Amsterdam [27]. A collaborative phylogenetic study revealed that these locally reported outbreaks were in fact part of one larger interconnected European transmission network [22].…”
Section: As Well As In the Unitedmentioning
confidence: 77%
See 2 more Smart Citations
“…Molecular typing of HCV isolates confirmed the presence of MSM-specific transmission networks in London [25], Paris [26] and Amsterdam [27]. A collaborative phylogenetic study revealed that these locally reported outbreaks were in fact part of one larger interconnected European transmission network [22].…”
Section: As Well As In the Unitedmentioning
confidence: 77%
“…However, recent outbreaks of acute HCV among HIV-positive MSM who deny IDU suggest that the epidemiology of HCV transmission is changing in this population. In several European countries [25][26][27] …”
Section: Hepatitis Bmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 The sexual transmission of HCV is ineffi cient, and the exact risk related to different types of sexual activity is unknown; nevertheless, it has been increasing among HIV-infected men who have sex with men (MSM). 8 The introduction of highly active antiretroviral therapy (HAART) has signifi cantly improved life expectancy of HIV-infected patients; however, the consequences of hepatitis C have become more apparent, as a result either of decompensated cirrhosis or hepatotoxicity due to HAART. 9,10,11 The interaction of those viruses has been the object of great concern, being considered one of the most important public health problems faced by health professionals and authorities worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…İntravenöz ilaç kullanımı olan HIV/AIDS hastalarında HCV ko-enfeksiyonu %50-95 arasında görülmüştür [18] . Bununla birlikte HCV cinsel yolla nadir bulaşmasına rağmen bazı çalışmalar HIV ile enfekte homoseksüellerde cinsel yolla bulaş riskinin yüksek olduğunu vurgulamışlardır [19][20][21] . Çalışmamızdaki üç hastanın ikisinde (%66) intravenöz ilaç kullanımı ve heteroseksüel ilişki öyküsü vardı.…”
Section: Discussionunclassified